Consensus statements from the Hong Kong Urological Association and the Hong Kong Society of Uro-Oncology on the management of muscle-invasive and advanced urothelial carcinoma - Poon, Darren M.C.; Chiu, Peter K.F.; Chan, Marco T.Y.; Ho, Brian S.H.; Law, K.S.; Leung, Angus K.C.; Leung, Clarence L.H.; Na, R.; Wong, Kenneth C.W.; Wu, Philip Y.; Kwong, Philip W.K.; Teoh, Jeremy Y.C. (Frontiers in Oncology, 2025)
BackgroundMuscle-invasive and advanced urothelial carcinoma (UC) are notorious for their high propensity for recurrence and metastasis. Recent advances in novel medications, surgical procedures, and radiotherapy techniques have substantially transformed the treatment landscape of muscle-invasive and advanced UC. It is crucial to navigate the optimal management approaches for muscle-invasive and advanced UC through the increasingly complex matrix of variables.MethodsTwo professional organisations convened a consensus panel of six urologists and six clinical oncologists with extensive experience in treating urological malignancies. They reviewed the literature on the management of i) non-metastatic, muscle-invasive, and locally advanced UC of the bladder; ii) locally advanced upper tract UC (UTUC); and iii) unresectable locally advanced or metastatic UC (mUC). The panel held multiple meetings to discuss and draft consensus statements using the modified Delphi method. Each drafted statement was anonymously voted on by every panellist. A consensus statement was accepted if ≥ 80% of the panellists chose ‘accept completely’ or ‘accept with some reservation’ from the five options, which also included ‘accept with major reservation’, ‘reject with reservation’, and ‘reject completely’.ResultsThe panel reached a consensus on 63 statements based on current evidence and expert insights. These statements addressed the considerations for different treatment modalities, including surgical approaches, radiotherapy, radiosensitisers, platinum-based chemotherapy, immune checkpoint inhibitors, and antibody–drug conjugates, in the management of different disease entities, including muscle-invasive UC of the bladder, cN1 disease, locally advanced UTUC, unresectable locally advanced/mUC, and oligometastatic bladder cancer.ConclusionThese consensus statements are anticipated to serve as a practical recommendation for clinicians in Hong Kong, and possibly the Asia-Pacific region, regarding the management of muscle-invasive and advanced UC.